USE OF NARCOTICS SUPPORTS RISK BEHAVIORS - Rico Januar Sitorus (Faculty of Public Health, Sriwijaya University, 2016)
Background: Drug abuse is a public health issue it is very important because it can lead to dependence, economic loss, loss of health and social impacts of drug abuse provides changes to the behavior of the user. Changes in behavior of drug users were more likely to negative behaviors that contribute to good health problems or social relations. The objective of this study is describe the use of narcotics support risk behaviors Method: This paper used a study literature from various source related to use of narcotics. Result: Research has shown that smoking and drinking behaviors associated with drug abuse. Risky sexual behavior is also often committed by drug addicts. Risky behaviors are very bad for the physical and psychological health of drug addicts. The adverse effects that can occur from the misuse of these substances, namely impairment of health due to the dependency can lead to death for the wearer, the destruction of the future generation to remember the majority of users are young people, and in certain circumstances can result in transmission of HIV/AIDS infection. Conclusion: To prevent the adverse effects resulting from the use of narcotics and risk behaviors, it is recommended to increase self-efficacy, family support for recovery, distancing themselves from the influence of the previous social groups and undergo rehabilitation.